An Exploration of Earnings Management Based on Green Investments and Financial Risk - Nugroho, Mulyanto; Agustono, Dyah Oktaviani Sulistyaningrum; Rahmiyati, Nekky (Fakultas Ekonomi Universitas Samudra, 2025)
In an era of globalization that increasingly prioritizes sustainability, green investment-based earnings management has become an important topic in the world of business and finance. This research was conducted with the aim of exploring earnings management based on green investment and financial risk. The method used in this research is a quantitative approach with a sample of 25 SRI-KEHATI indexed companies selected by purposive sampling. The research results show that green investment has no significant effect on earnings management and financial risk has a significant effect on earnings management. Based on these results, it is recommended for future researchers to consider using alternative stock indices, such as LQ45, Kompas100, JII, and others. Additionally, it may be useful to differentiate between companies operating in manufacturing and banking, which may yield different research results.